Doctores en derecho por la Universidad Central. Catálogo de tesis doctorales 1847-1914 - Miguel Alonso, Aurora (Historia del Derecho, 2021)
This work compiles the doctoral theses presented at the Faculty of Law of the Central University of Madrid between 1847, the year in which the modern thesis was created in the Spanish university, and 1914, expanding this second edition with the records of the graduates who achieved the degree of doctor in this same faculty in the immediately preceding period, 1845 to 1847, and in which the presentation of a doctoral thesis was not yet required; therefore, the total number of records in this edition is increased to 3,092, compared to the 3,073 of the previous edition. The catalogue is arranged chronologically, which makes it easier for the researcher to sequence the evolution of an important part of the country's legal scientific production, and the research trends of the Faculty in the period studied. The catalogue is accompanied by an extensive introduction which studies the legislation governing doctorates in liberal Spain and the methodology followed in compiling the catalogue. It closes with several appendices that complement the study: a table of the teaching staff of the doctoral courses (by course and onomastic), a table of the syllabuses in force over the almost seventy years covered by the work, and a graph of the theses presented by year. The final index of graduates facilitates immediate consultation of the catalogue.